Designing a Fiber to the Home (FTTH) Network Using Google Earth in Taman Sekata Indah Housing Estate - Nurzanah, Laila; Hasibuan, Muhammad Fikry Hasrul; Mujahid, Putra Edi; Soselisa, Yopie Lahardo (Jurnal Media Teknik Elektro dan Komputer, 2024)
This research discusses the design of a fiber-to-the-home network in Taman Sekata Indah Housing, Tanjung Selamat, Sunggal, Deli Serdang Regency, North Sumatra 20351 using the Google Earth Pro application. This research aims to find out in detail how to design a fiber to the home network starting from the boundaries of the area and the data collection of the number of buildings in the area. area restrictions and data collection on the number of buildings in the area, designing the Optical Distribution Point (ODP) pole. The research methods include making a flow chart and searching for data sources using observation, interviews, and case studies. In this research, the data obtained in the form of the total number of buildings in the surrounding area, and the number of distribution cable lengths that must be provided during installation. Length of distribution cable that must be provided when installing a fiber network to the home, as well as the determination of the Optical location point. to the house, as well as the determination of the location point of the Optical Distribution Point (ODP) and the Optical Distribution Point (ODP) and Optical Distribution Cabinet (ODC) pole. In detail and detail.